2005
DOI: 10.1074/jbc.m506718200
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Regulatory Element-binding Proteins Activate Insulin Gene Promoter Directly and Indirectly through Synergy with BETA2/E47

Abstract: Insulin gene expression is regulated by pancreatic ␤ cell-specific factors, PDX-1 and BETA2/E47. Here we have demonstrated that the insulin promoter is a novel target for SREBPs established as lipid-synthetic transcription factors. Promoter analyses of rat insulin I gene in non-␤ cells revealed that nuclear SREBP-1c activates the insulin promoter through three novel SREBP-binding sites (SREs), two of which overlap with E-boxes, binding sites for BETA2/ E47. SREBP-1c activation of the insulin promoter was marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…It is, thus, conceivable that the proximal (GL1/GL2 containing) and distal (GL3 containing) regions of the promoter may physically interact to provide cooperative regulation of transcription. This is in agreement with previous studies that have suggested that insulin responsiveness of glucagon gene expression is dependent on interactions between proximal and distal elements (38), possibly through the formation of a DNA looping structure as found in previous studies (39,40). Finally, expression of a FoxO1.eGFP chimera increased the basal activity of the PPG promoter.…”
Section: Expression Of Foxo1 In Isolated Mousesupporting
confidence: 81%
“…It is, thus, conceivable that the proximal (GL1/GL2 containing) and distal (GL3 containing) regions of the promoter may physically interact to provide cooperative regulation of transcription. This is in agreement with previous studies that have suggested that insulin responsiveness of glucagon gene expression is dependent on interactions between proximal and distal elements (38), possibly through the formation of a DNA looping structure as found in previous studies (39,40). Finally, expression of a FoxO1.eGFP chimera increased the basal activity of the PPG promoter.…”
Section: Expression Of Foxo1 In Isolated Mousesupporting
confidence: 81%
“…RIP-luciferase reporter plasmid and sterol-regulatory element (SRE)-luciferase reporter plasmid were produced as previously described (22,23).…”
Section: Expression Plasmid and Reporter Plasmidsmentioning
confidence: 99%
“…The cells were transfected with a SRE-luciferase reporter plasmid (500 ng) and a pRL-SV40 plasmid (50 ng, Promega) using Lipofectamine 2000 reagent (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions as previously decribed 15) . After 4-hour incubation, the cells were subjected to statin treatment as described above.…”
Section: Transfection and Luciferase Assaysmentioning
confidence: 99%